Accelerated cellular senescence in solid tumor therapy - Wu, P.C.; Wang, Q.; Grobman, L.; Chu, E.; Wu, D.Y. (Experimental Oncology, 2012)
Accelerated cellular senescence (ACS) is an emerging concept that implicates sustained, telomere-independent cell cycle arrest of neoplastic cells in response to chemotherapeutic agents, ionizing radiation, oxidative stress, or the presence of selective oncogenic stimuli. Recent evidence suggests that a subset of tumor cells induced in a state of reversible ACS can escape cell cycle arrest and resume proliferation accounting for cancer progression. The purpose of this review is to describe our current understanding of ACS including signaling pathways of senescence escape, role of senescence biomarkers, and rationale for senescence-based therapy. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.